“In the Midst of Chaos There Was Shape”: Formalist Aesthetics and Ekphrasis in To the Lighthouse - Liu Kehan (American, British and Canadian Studies Journal, 2023)
Virginia Woolf’s autobiographical novel To the Lighthouse explicitly connects itself with Bloomsbury formalist aesthetics, with a special acknowledgement of Roger Fry’s formalist influence. This essay focuses on the influence of Fry’s formalist principles on To the Lighthouse, but additionally proposes a reorientation of reading that argues for Woolf’s modifications of formalism, which is concretized as the reconciliation of formalism and everyday life, where everyday life is specified as Woolf’s notion of “moments of being.” The essay contends that such a reconciliation is facilitated by representation and thus adopts James Heffernan’s theory of ekphrasis to analyse Lily Briscoe’s painting. Drawing on Heffernan’s definitions of ekphrasis, this essay regards the formalist elements in Lily’s picture as representational but not pictorial, whereas the object represented in Lily’s picture – in the text, Mrs. Ramsay – is of second-degree representationality, which spells out as intimacy and unity in terms of human relations. With intimacy and unity as core values in her mind, Lily eventually manages to represent Mrs. Ramsay’s being until “there she sat.”